PENGARUH PROFITABILITAS TERHADAP KETERLAMBATAN PUBLIKASI LAPORAN KEUANGAN AUDITAN DENGAN AUDIT REPORT LAG SEBAGAI VARIABEL INTERVENING - Nursepdianisyah, Sonia; Sumunar, Kurnia Indah (Lembaga Pengembangan Kinerja Dosen, 2022)
Companies that have been listed on the Indonesia Stock Exchange are required to submit audited annual financial reports to the public, which information will then be used by interested parties for consideration in making decisions. However, in fact not all issuers are able to publish their annual financial reports on the Indonesia Stock Exchange. So that this study aims to determine the effect of financial performance on the delay in the publication of audited financial statements mediated by audit report lag. The object of research is issuers with consumer cyclicals and consumer non-cyclicals sectors and late in publishing their audited financial reports, observation period 2017-2021. The sampling technique used purposive sampling and resulted in 46 samples. The research method used is statistical t test, path analysis and Sobel test using the help of the IBM SPSS version 26 program. The results of this study indicate that profitability has an effect on audit report lag, profitability has no effect on delays in the publication of audited financial statements, audit report lag affects delays publication of audited financial statements, and audit report lag succeeded in mediating profitability against the delay in publication of audited financial statements.